2014
DOI: 10.26719/2014.20.10.596
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical inactivity and perceived barriers to physical activity among health college students, south-western Saudi Arabia

Abstract: Physical inactivity is a public health problem in Saudi Arabia. A cross-sectional study was carried out to evaluate the pattern of physical activity, predictors of physical inactivity and perceived barriers to physical activity among health college students in King Khalid University. A total of 1257 students (426 males and 831 females) were recruited. The Arabic short form of the International Physical Activity Questionnaire was used. Overall, 58.0% of the students were physically inactive. Only 13.4% of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
108
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 30 publications
16
108
2
4
Order By: Relevance
“…Generally, university students do not have lifestyles consistent with healthy living (5,6), thus, health professionals in training are not being credible health advocates, given academic pressures, stress, scarce resources and limited time to devote to healthy pursuits. One recent study of 787 Kuwaiti university students reported overweight and inactivity as health priorities, consistent with findings across universities in the Middle East (7,8).…”
Section: Introductionsupporting
confidence: 56%
“…Generally, university students do not have lifestyles consistent with healthy living (5,6), thus, health professionals in training are not being credible health advocates, given academic pressures, stress, scarce resources and limited time to devote to healthy pursuits. One recent study of 787 Kuwaiti university students reported overweight and inactivity as health priorities, consistent with findings across universities in the Middle East (7,8).…”
Section: Introductionsupporting
confidence: 56%
“…Esses achados divergem do estudo realizado com 5.461 universitários de uma instituição pública do estado da Bahia, em que os universitários dos últimos semestres da graduação relataram um maior número de barreiras percebidas para a prática de AF 16 . Uma possível explicação deve-se ao fato de que na instituição onde foi realizado o presente estudo, grande parte dos universitários matriculados em semestres finais estarem cursando um menor número de disciplinas e/ou disciplinas na modalidade estudo dirigido, culminando em um menor tempo gasto com atividades acadêmicas.…”
Section: Discussionunclassified
“…26 Additional factors that have been described as barriers to routine exercise include time limitations and a reliance on cars for transportation. 27,28 Previous studies have also reported lack of time as a barrier to exercise. 22,29,30 One such study reported that 80% of college students in Dammam, Saudi Arabia, felt that lack of time restricted their ability to partake in physical activity.…”
Section: Discussionmentioning
confidence: 99%